Somatization, psychological distress, and quality of life across fibromyalgia, irritable bowel syndrome, and their comorbid phenotype: a cross-sectional clinical comparison - Prospero, Laura; Riezzo, Giuseppe; Laselva, Gaetana; D’Attoma, Benedetta; Ignazzi, Antonia; Goscilo, Francesco; Bianco, Antonella; Franco, Isabella; Verrelli, Nicola; Bagnato, Claudia Beatrice; Coletta, Sergio; Refolo, Maria Grazia; et al. (Frontiers in Psychology, 2025)
BackgroundFibromyalgia (FM) and irritable bowel syndrome (IBS) are increasingly recognized as disorders involving central sensory processing and gut–brain axis dysregulation, often accompanied by autonomic and psychological disturbances.MethodsWe investigated whether patients with comorbid FM and IBS (FM + IBS) experience greater somatization and reduced quality of life (QoL) compared to those with either condition alone, and if somatization serves as a predictor of gastrointestinal (GI) symptom severity. In this cross-sectional study, 53 adults (mean age 47.4 ± 1.3 years; 48 women) were classified into three groups: FM-only (n = 13), IBS-only (n = 18), and FM + IBS (n = 22). Participants completed validated assessments including the IBS Symptom Severity Scale, the Symptom Checklist-90-Revised, the Perceived Stress Scale, and QoL measures (SF-36, WHOQOL-BREF). Group differences were analyzed using the Kruskal-Wallis test, and predictors of IBS severity were identified via stepwise multiple linear regression.ResultsFM-only and FM + IBS patients reported similar levels of pain, fatigue, and functional impact. GI symptoms were mild in FM-only patients but moderate in IBS-only and FM + IBS groups, with large effect sizes for psychological distress, mental health, and IBS severity. While FM + IBS participants showed slightly higher FM-related symptom scores, differences were not statistically significant. Somatization and diagnostic group independently predicted IBS severity, together explaining 50% of the variance.ConclusionThese findings demonstrate a progressive increase in somatization and a parallel decline in QoL across the spectrum from IBS-only to FM-only to FM + IBS, supporting the concept of functional somatic syndromes as a continuum. Incorporating routine assessment of somatization and QoL impairment may help identify patients at higher risk of treatment resistance and facilitate timely, integrated biopsychosocial strategies, including cognitive-behavioral and neuromodulatory interventions.